Prevalence and related factors of excessive daytime sleepiness among bus drivers in Bangkok - ธนธิติกร ชุลีกร; ศุภพงษ์ สุนทร; เจียมจริยธรรม ณัฐพงษ์ (Disease Control Journal, 2013)
Excessive daytime sleepiness (EDS) is common condition worldwide with respect to errors, accidents, absenteeism, reduced productivity and impaired personal or professional life. It can be caused by disorders such as obstructivesleep apnea (OSA), narcolepsy, and idiopathic hypersomnia. The diagnosis of this conditions still be the problem so the incidents of EDS is lower than it should be. This cross-sectional survey aimed to evaluate the prevalence and related factors of excessive daytime sleepiness among bus drivers in Bangkok Mass Transit Authority (BMTA). The data were collected from 241 bus drivers during January 2013 by using self-administrated questionnaire with evaluating excessive daytime sleepiness by Epworth sleepiness scale. The response rate in this study was 83 °/o. The result showed that the prevalence of excessive daytime sleepiness was 86 °/o with mean of Epworth sleepiness scale of 12.68 Factors which statistically significant associated to excessive daytime sleepiness (p<0.05) included: body mass index; history of using hypnotic drug; smoking history; alcohol drinking history; coffee drinking history; number of workday; period of work; number of sleep hours on weekday and weekend; wake at night on weekday and weekend; lying on right and left side; sound of snoring; nocturia; shaking leg when sleep; dreaming This survey found that the prevalence of excessive daytime sleepiness in bus drivers was higher than other studies and the most associated factors were alcohol drinking and smoking. The cessation of smoking and alcohol drinking project should be launched as soon as possible. The screening of excessive daytime sleepiness should be performed.